Factors That Influence Brand Awareness of The Purchase Intention of Indomie Instant Noodle - Adisti Yolanda; Budi Astuti (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to examine and analyze the influence of product packaging, the attractiveness of advertising, distribution intensity, and sales promotion on brand awareness and purchase intention on Indomie instant noodle products. In sampling, this study uses convenience sampling techniques. The number of samples in this study was 140 respondents. The statistical analysis technique used in this study is Structural Equation Modeling (SEM) with SmartPLS software version 3.2.9. The results of data analysis in this study prove that product packaging and distribution intensity has a positive and significant effect on brand awareness. Brand awareness also has a positive and significant effect on purchasing intentions. However, the attractiveness of advertising and sales promotion has no effect on brand awareness.